A chegada do som nos cinemas de São Paulo segundo a Folha da Manhã (1928-1933) - Valencise, João Miguel (Universidade Federal de São Carlos, 2012)
This dissertation focuses on study and observation of the period of transition from silent films to sound films in movie theaters at São Paulo City, as recorded by the pages of Folha da Manhã newspaper between 1928 and 1933. It aims to investigate and understand how adaptations to this new technology were proceeded in exhibitors market. Besides this strictly technical question (including the availability of national projection equipment), this study sought to offer a narrower look at several aspects related to this process, such as the several ways of presentation of the cinematographic product, the presence of national movie pictures at the 1920s and the conformation of movie market at São Paulo state capital.
Keywords: Cinema - história; Som; Cinema sonoro; Cinema brasileiro; Mercado cinematográfico; Sound; Sound films; Brazilian movie pictures; Exhibitors market; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA